Remembering the dead, reconciling the living:: George Floyd and All Saints’ Day - Belcher, Kimberly Hope (Stellenbosch Theological Journal, 2024)
Rituals advancing reconciliation often do so by recalling a shared history or proposing a shared future. Racial reconciliation in the United States and recovery from the clergy sexual abuse crisis must reckon with how the past can be justly remembered. The George Floyd Global Memorial in Minneapolis, Minnesota, occupies a space of remembrance, raising up a representative victim of police violence as a symbolic ancestor. The All Saints’ and All Souls’ Day monastic liturgies at St John’s Abbey in Collegeville, Minnesota, remember the dead and a future that transcends contemporary divisions. This article will explore how gestures toward an eschatological future in both of these memorial rites frame the memory of the past and mediate the relationship between the living and the dead amid a fragile movement towards reconciliation.